AGAINST STEREOTYPE AND DISCRIMINATION OF THE BLACK IN JOHN LEE HANCOCK'S THE BLIND SIDE MOVIE (2009): A SOCIOLOGICAL PERSPECTIVE - SAPUTRI, ELISA DENIS (2011)
The research is aimed to know the struggle of Against Stereotype and Discrimination of The Black In John Lee Hancock's The Blind Side Movie by using sociological perspective. Therefore, the study analyzes the movie in terms of its structural elements and based on the sociological perspective. This research belongs to descriptive qualitative study. In this method, the writer uses two data sources: they are primary data and secondary data source. The primary data source and the object of the study is the movie The Blind Side, meanwhile the secondary data sources are any books of literature and sociology and websites related to this research. The writer collects the data from both primary and secondary data sources in a short of document evidence. The story comes to the following conclusion: First, based on structural analysis, it is apparent that in The Blind Side movie, John Lee Hancock conveys message that everyone deserves to be successful disregarding the race, ethnicity, culture and religion. Second, it is clear that there is a firm relation between this movie and the social reality in America in early twenty first century. The Blind Side shows that some ethnic minorities in America especially black people still get stereotype and discrimination in their life.